DESIGN AND CONSTRUCTION OF A MEMBRANE REACTOR SILVER FOR THE STUDY OF OXYGEN PERMEABILITY - Cjuno H., Jesús A. (2007)
To study the permeability of oxygen through a membrane of silver (thickness 0.13 mm) and the definition of parameters, it has designed and constructed a reactor formed by a cone silver membrane inserted into a cylindrical glass tube borosilicate. This assembly is assembled within a cylindrical thermostated oven electronically. The membrane reactor was conentado to an oxygen tank, and two peristaltic pump mercury manometer, enabling control of inflow of methanol, the temperature and internal pressure and desorption of the permeated oxygen. With this device have been performed subsequent studies of oxidative reactions in primary alcohols.